PENGARUH LKS TERINTEGRASI SISTEM GERAK TUBUH MANUSIA TERHADAP HASIL BELAJAR FISIKA SISWA DALAM PEMBELAJARAN KOOPERATIF TIPE THINKING ALOUD PAIR PROBLEM SOLVING DI KELAS XI SMAN 5 PADANG - Maharani Erika Putri; Syakbaniah Syakbaniah; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2016)
One of the factors that lead to low yields physics student learning is the lack of ability in problem solving and learning physics at school is not linked to the conditions faced by the students. How to overcome this problem is to use an integrated LKS motion system of the human body with the type cooperative learning model Thingking Aloud Pair Problem Solving (TAPPS). This study aims to Investigate the effects and contribution of LKS integrated motion system of the human body to the learning outcomes of students of class XI SMAN 5 Padang.This type of research is a Quasi Experiment Research by design Randomized Control Group Only Design. The study population was a class XI SMAN 5 Padang enrolled in the academic year 2015/2016. The results showed physics learning outcomes on average the experimental class higher than the control class. Based on the equality test two mean using the t test, obtained thitung > ttabel. This means that the null hypothesis is rejected and the alternative hypothesis is accepted. Based on the correlation analysis, obtained contributions LKS integrated motion system of the human body for the cognitive domain was 89.47%, 43.18% are affective and psychomotor is 52.83%. Conclusion of the study is the hypothesis that, There is a significant influence LKS terintegrai motion system of the human body to the learning outcomes of students in the physics Cooperative learning model type Thingking Aloud Pair Problem Solving in class XI SMAN 5 Padang on the real level of 0.05, and There is a strong contribution LKS yanng integrated motion system of the human body to the learning outcomes of students in the physics Cooperative learning model type Thingking Aloud Pair Problem Solving in class XI SMAN 5 Padang, acceptable